Récits. - Blanchet, Jean-Paul (Meymac : Abbaye Saint-André Centre d'Art Contemporain, 2002)
Barbier, Gilles ; Barré, Virginie ; Bartoloméo, Joël ; Blume, Bernhard Johannes ; Blume, Anna ; Bregeaut, Anne ; Burgin, Victor ; Calle, Sophie ; Chales de Beaulieu, Susan ; Cognée, Philippe ; Corillon, Patrick ; Declercq, Alain ; de Pietri, Paola ; Desgrandchamps, Marc ; Corcia, Philip Lorca di ; Giloux, Pierre-Jean ; Kuntz, Raphaël ; Höller, Parreno & Tiravanija ; Huber, Thomas ; I.A.T. ; Joseph, Pierre ; Kentridge, William ; Klauke, Jürgen ; Lafont, Suzanne ; Mahler, Rachel ; Mik, Aernout ; Moffatt, Tracey ; Monory, Jacques ; Mréjen, Valérie ; Paradeis, Florence ; Petitgand, Dominique ; Perramant, Bruno ; Rebufa, Olivier ; Tan, Fiona ; Trouvé, Tatiana ; Tschäpe, Janaina ; Zivic, Gregor
Frans
Récits, Abbaye Saint-André, Centre d'Art Contemporain, Meymac-Corrèze, du 7 juillet au 27 octobre 2002
boek